¡A desalambrar! Resistencias, desigualdades e itinerarios posibles en sociedades latinoamericanas - Cristina Basconzuelo, Celia; Díaz Esteves, Víctor; Aravena Carrasco, Antonio (Internacional del Conocimiento, 2022)
The title of this book is not innocent, it condenses the communicative intention of editorial work. It offers critical perspectives on some of the problems of the societies of the continent and, at the same time, sets out ways of solving it. In this sense, in the intention of the compilers lies an enormous wealth. Its pages are built with the result of the hard work of academics and researchers from Argentina, Brazil, Chile, Colombia, Mexico, Guatemala and Uruguay, forming a book that allows us to approach some dimensions that are configured in the various territories with a complex look at through current problems. It is therefore a production that we can place within the developments framed in the so-called epistemologies of the South.